ANALISIS KONTRIBUSI PETANI PEREMPUAN TERHADAP PENDAPATAN KELUARGA DI DESA BEKALAR KECAMATAN KANDIS KABUPATEN SIAK - Antin Kurnyasih; Bintang Akbar Azhari; Riski Halomoan Siregar; Purnama Ramadani Silalahi (Pusat Riset dan Inovasi Nasional, 2023)
One of the causes that encourage women (wives) to work in the public sector or to become breadwinners for their families is family poverty. The agricultural industry plays an important role in creating employment opportunities for women. Likewise, the agricultural sector is the main source of income for most women in Bekalar Village; women farmers in Bekalar Village are involved in agriculture from planting to harvesting; This cannot be separated from the role of women. Because women's involvement in agriculture increases family income, this study will examine how the contribution of female farmers to family economic income in Bekalar Village. This research is a descriptive research that tries to describe the objects and phenomena studied, namely how the contribution of women farmers to the economic income of families in Bekalar Village, Kandis District, Siak Regency. Based on the findings of this study, women farmers in Bekalar Village have a contribution to the family's economic income in terms of women farmers being able to meet the needs of the family. Women farmers working in the agricultural industry face a number of challenges, including unpredictable market prices for agricultural products and prejudice against women, who have dual responsibilities in the household.